Supernatural Powers And Human Struggles In Stephen King’s “Doctor Sleep” (Texas Journal of Philology, Culture and History, 2025)
Scholars have given King little notice as a writer of magical realism as a narrative strategy. In this article highlights of supernatural powers and human struggles in Stephen King’s “Doctor sleep”.